ACHIEVING HARMONY IN THE RELATIONSHIP BETWEEN HUMANS AND THE ENVIRONMENT: ECO-FOCUSED LEARNING TECHNOLOGIES (Innovative professional education, 2022)
Modern ecology includes layers of humanitarian and philosophical problems. The need for new pedagogical technologies, in particular eco-oriented ones, is caused by the new needs of society, aimed at achieving harmony in the relationship between man, society and nature. Eco-oriented learning technology is presented as a system of scientifically sound actions and interaction of elements of the educational process, the implementation of which guarantees the achievement of learning goals aimed at achieving harmony in the relationship between man, society and nature.
Keywords: ecological education; ecology; professional education; pedagogical technologies; eco-oriented learning technologies